"Ductile to brittle" transition in thermally stable antigorite gouge at mantle pressures. Issue 3 (28th March 2016) - Proctor, Brooks; Hirth, Greg
Abstract: General shear experiments on antigorite‐rich serpentinite show a transition from ductile (distributed) to brittle (localized) deformation with increasing temperature from 300°C to 500°C at confining pressures from 1 to 2 GPa. The coefficient of friction associated with slip along fractures decreases from 0.23 to 0.07 with an increase in temperature from 300°C to 500°C. Velocity stepping experiments exhibit a positive rate dependence, as parameterized by a‐b values, that decrease modestly with increasing temperature from ~0.015 at 300°C to ~0.01 at 500°C. Fractures contain fine‐grained foliated antigorite, and there is no evidence of dehydration. All samples have a moderate foliation and show microstructural evidence for both plastic and brittle deformation mechanisms. Under certain conditions the transition to brittle deformation, at high pressures and temperatures in antigorite, might generate earthquakes, which could explain the occurrence of some intermediate‐depth seismicity within subduction zones in serpentinized regions that are too cold to induce dehydration. Key Points: Antigorite has an inverted brittle to ductile transition Antigorite friction is strongly temperature dependent at mantle pressures Velocity dependence decreases with increasing temperature